Factors promoting emotional‐behavioural resilience and adjustment in children exposed to intimate partner violence: A systematic review - Alison Fogarty; Catherine E. Wood; Rebecca Giallo; Jordy Kaufman; Michelle Hansen (Australian Journal of Psychology, 2019)
Background Children exposed to intimate partner violence (IPV) are at heightened risk of emotional and behavioural problems. However, not all children exposed to IPV experience difficulties. Many display positive wellbeing and development despite experiencing this adversity. Objective This is the first known article to systematically review the existing literature on the factors associated with emotional and behavioural resilience and positive functioning in children exposed to IPV. Method This review was registered at the PROSPERO international prospective register of systematic reviews, registration number CRD42016037101. Four databases were searched (Embase, Web of Science, Psychinfo, and Medline) for peer‐reviewed articles assessing factors associated with positive outcomes for children (aged between 0 and 12-years) who had been exposed to IPV. Retrieved articles were screened for eligibility by two independent reviewers. Results Of the 1,365 retrieved articles, 15 were eligible for inclusion. Results showed that maternal mental health was a significant predictor of resilience in children exposed to IPV. Preliminary evidence was found for emotion coaching, parenting, and child temperament. Broader socio‐contextual factors were largely neglected across the articles reviewed. Conclusion The findings from this review highlighted that there is still much to be learned about what helps children display resilience when exposed to IPV and what can be done to foster this resilience.